POST-PANDEMIC GOVERNANCE, FINANCE, AND INNOVATION IN INDONESIAN HEALTHCARE FIRM VALUE - Elly Astuti; Elana Era Yusdita; Putri Widianti; Adynda Surya Aprilya Kinanthy; Irma Wahyu Lestari; Claratu Wangi (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2026)
This research examines the Indonesian healthcare sector's efforts to enhance efficiency and competitiveness through digital transformation, amid challenges such as limited service access and resource inequality. It highlights the importance of innovation and corporate governance, particularly gender diversity, as essential elements of corporate sustainability. The study investigates factors influencing firm value, specifically financial performance, governance mechanisms, and innovation. Using multiple linear regression, the findings indicate that profitability, capital structure, firm size, and institutional ownership positively affect corporate valuation. In contrast, the ratio of intangible assets used as a proxy for innovation shows a negative relationship, while liquidity and gender diversity do not have a significant impact. These results suggest that the economic benefits of digital innovation and diversity have not been fully recognized in market valuations, highlighting ongoing challenges in translating strategic initiatives into value. The research contributes to existing scholarship by reinforcing the roles of financial performance and corporate governance as key drivers of firm value, especially in the rapidly evolving digital transformation landscape of emerging economies.